Pengaruh TATO, CR, dan DER terhadap ROA pada PT Telekomunikasi Indonesia Tbk Tahun 2016-2024 - Ratni, Kadek Indrawati; Yasa, I Komang Widya Purnama (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the influence of Total Asset Turnover (TATO), Current Ratio (CR), and Debt-to-Equity Ratio (DER) on Return on Assets (ROA) at PT Telekomunikasi Indonesia Tbk during the 2016–2024 period. This study employs a descriptive quantitative approach using quarterly data (n = 36 observations) obtained from the company’s official financial statements and the Indonesia Stock Exchange. The analysis was conducted using multiple linear regression with SPSS version 27, accompanied by classical assumption tests to ensure the model’s validity. The results indicate that TATO has a significant negative effect on ROA (p = 0.006; t = -2.965), suggesting that increased asset utilization efficiency is actually followed by a decline in profitability. This occurs due to high depreciation expenses and long-term digital infrastructure investments that have not yet fully generated profits. Furthermore, CR does not have a significant effect on ROA (p = 0.677; t = -0.420), indicating that liquidity is not a major determinant of profitability in the telecommunications industry, which has stable cash flows. Meanwhile, the DER has a significant negative effect on ROA (p = 0.045; t = -2.089), meaning that reliance on debt reduces profit efficiency due to increased interest expenses. Simultaneously, TATO, CR, and DER have a significant effect on ROA (F = 5.479; p = 0.004) with an R² value of 0.339, indicating that the three variables explain 33.9% of the variation in profitability. These findings underscore the importance of managing capital structure and operational cost efficiency to maintain profitability amid digital transformation.